Boerhaave’s syndrome: A case report - Hemalatha, Jalli; Jayasree, Kurupatha Menatha (Indian Journal of Case Reports, 2026)
Boerhaave’s syndrome, defined as spontaneous full-thickness oesophageal rupture, represents a rare yet critical surgical emergency triggered by abrupt increases in intraoesophageal pressure, most commonly after intense vomiting.This results in contamination of the mediastinum by gastric contents, with swift advancement to sepsis absent timely intervention. Here, we describe a 39-year-old man with longstanding alcohol dependence who developed intense retrosternal pain and shortness of breath after an episode of violent retching. Imaging via chest X-ray and computed tomography demonstrated left hydropneumothorax alongside mediastinal air, diagnostic of oesophageal disruption. Treatment involved broad-spectrum antibiotics, tube thoracostomy, acid suppression with proton pump inhibitors, and parenteral nutrition. Given his early arrival and favorable response, operative repair was avoided in favor of nonoperative care. Swift recognition and coordinated specialist input remain vital to improving survival in this condition